2020
DOI: 10.1088/2632-959x/ab8961
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled monolayer formation of pentamers-like molecules onto FCC(111) surfaces: the case of curcuminoids onto Au(111) surface

Abstract: The adsorption of rigid straight electrically polarized pentamers over a FCC(111) surface is studied. The model was inspired by the deposition of 2-thiophene molecules over the Au(111) surface, which was previously characterized by experimental techniques and simulated under the frame of the density functional theory. We now obtain and report the charge distribution of the molecule which allows to propose a deposition model followed by Monte Carlo simulations over an ad-hoc lattice gas model. We show that for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
(74 reference statements)
2
2
0
Order By: Relevance
“…As mentioned, in our previous paper [41] we found that the system described previously experiences an isotropic-nematic phase transition at a determined critical coverage. Figure 2 shows snapshots of the system experiencing this phase transition.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…As mentioned, in our previous paper [41] we found that the system described previously experiences an isotropic-nematic phase transition at a determined critical coverage. Figure 2 shows snapshots of the system experiencing this phase transition.…”
Section: Resultssupporting
confidence: 70%
“…In a simplified way we propose that these interaction energies conveniently expressed in k B T (k B is the Boltzmann constant) units, are w HH = 1.0, w HC = 0.5w HH = 014133-3 0.5, and w CC = 1.5w HH = 1.5. As explained in our previous paper [41] (see for example Fig. 2 of that paper and the discussion around it), this set of values manages to reproduce very well the interaction energies of two adsorbed 2-thiophene molecules on its most representative relative orientations, as calculated by Flores et al [42] by DFT calculations.…”
Section: A Molecular Deposition and Lattice-gas Modelsupporting
confidence: 62%
See 2 more Smart Citations